Motivação e consequências das decisões: uma análise dos artigos 20 e 22 da Lei de Introdução às Normas do Direito Brasileiro – Lei nº 13.655/2018 – LINDB - Cammarosano, Flávia Giorgini Fusco (2021)
The thesis main theme is the motivation and the consequences of decisions as of the promulgation of the Law of Introduction to the Standards of Brazilian Law – n. 13.655/2018 – also known as LINDB, especially its articles 20 and 22. The study aims to examine how jurists and legal practitioners are adapting their activities to the new requirements coming from the LINDB. Its significance consists in the understanding of the inevitable changes brought by the concerned rule to the public administration, specially to the stewardship of choices and decisions issued by controllers and public managers. The hypothesis of the study is that the onset of LINDB provisions implies new standards to the motivation of administrative acts, reflecting on its validation. The changing of motivation standards inflicts additional difficulties and concerns to public managers and control agencies concerning accountability and punishment, for which reason it is essential to reflect upon and pondering on this subject. The challenges caused by LINDB legal innovations are found in many areas of Public Administration and, taking into account the need for a feasible methodological section, the thesis chooses to focus on the themes of motivation and consequences of decisions; for that purpose it uses the deductive method and promotes a qualitative research based on the review of legal literature and national legislation in the field of Administrative Law. Finally, as a result, the study provides general reflections towards the promotion of a better understanding of the new features, originating from LINDB advent, of the duty to motivate and of the legal, administrative and practical consequences of the decisions